2014
DOI: 10.1007/s10943-014-9837-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Islamic Intercessory Prayer on Warts

Abstract: The present study aimed to examine the therapeutic effects of Islamic intercessory prayer on warts. Forty-five participants who are mostly Muslims and infected with warts were randomized into three groups: Group-1 (uncertain, with intercessory prayer), Group-2 (uncertain, no intercessory prayer), and control group (informed, no intervention). Stress symptoms were also measured before and after prayer sessions for these three groups. The results revealed that there were no significant differences between the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…A similar study reported that the participants prayed to God via an intercessor (an imam) and their warts were thus recovered. The study also reported that no effects were seen in the participants who did not trust the intercessor's prayers (5). Therefore, believing is a key issue both for prayer and hypnosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A similar study reported that the participants prayed to God via an intercessor (an imam) and their warts were thus recovered. The study also reported that no effects were seen in the participants who did not trust the intercessor's prayers (5). Therefore, believing is a key issue both for prayer and hypnosis.…”
Section: Discussionmentioning
confidence: 88%
“…There is also another concept named ''intercessory prayer'', which means that a person performs prayer for the benefit of another person. Many people believe that intercessory prayer is very effective in recovering from illnesses (4,5), particularly in the Turkish society (6). In a study on the use of hypnoanalysis, 33 of 41 (80%) consecutive patients were cured, two were lost to follow-up, and six did not respond to treatment (7).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian terdahulu menunjukkan bahwa praktik keagamaan, termasuk shalat, dapat berperan sebagai sumber koping positif dalam mengatasi tekanan psikologis (Abu-Raiya & Pargament, 2015). Terapi shalat diklaim mampu memberikan rasa ketenangan, meningkatkan kepercayaan diri, dan mengurangi tingkat kecemasan pada individu (Roussi, 2012).…”
unclassified
“…Existem várias abordagens espirituais e religiosas atualmente utilizadas como terapêutica complementar. As preces intercessórias realizadas à distância, que podem ser com ou sem ciência do paciente, já foram realizadas em diversas doenças (Walker et al, 1997;Olver e Dutney, 2011;Hoşrik et al, 2014). Os resultados, porém apresentam-se contraditórios, alguns apresentando melhora nos sintomas avaliados (Olver e Dutney, 2011), outros neutros (Hoşrik et al, 2014) e outros ainda mostrando piora (Walker et al, 1997).…”
Section: Puchalski Et Al (2012)unclassified
“…As preces intercessórias realizadas à distância, que podem ser com ou sem ciência do paciente, já foram realizadas em diversas doenças (Walker et al, 1997;Olver e Dutney, 2011;Hoşrik et al, 2014). Os resultados, porém apresentam-se contraditórios, alguns apresentando melhora nos sintomas avaliados (Olver e Dutney, 2011), outros neutros (Hoşrik et al, 2014) e outros ainda mostrando piora (Walker et al, 1997). A conclusão geral desses estudos é que existem dificuldades metodológicas para fundamentar os argumentos e necessidade de mais estudos sobre o assunto.…”
Section: Puchalski Et Al (2012)unclassified